Dependence between volatility of stock price index returns and volatility of exchange rate returns under QE programs: Case studies of Thailand and Singapore - Puarattanaarunkorn O. (2017)
© Springer International Publishing Switzerland 2016. This study found the evidences of the dependence between the volatility of stock price index returns and the volatility of exchange rate returns measured against US Dollar and Japanese Yen, and the independence between the volatility of stock price index returns and the volatility of exchange rate returns measured against Euro, in both Thailand and Singapore, under the operation of QE programs. It also found that all bivariate copula of the volatility of stock price index returns—the volatility of Thai Baht/US Dollar exchange rate returns, and the volatility of stock price index returns—the volatility of Thai Baht/Japanese Yen of Thailand, had a degree of dependence greater than that of Singapore. This can be explained that the QE programs can affect capital flows to Thailand and Singapore, and also may have different effects on the volatility of each exchange rate returns and the volatility of stock price index returns, of the individual country. This information can be useful for policy makers and investors so that they can directly focus on avoiding adverse implications from the operation of QE programs, in terms of the risks incurred from the volatility of exchange rate returns and the volatility of stock price index returns.